Migration as an economic component of the European countries' development - Tetiana But (National Accounting Review)
Most European countries view migrants as individuals who can increase the country's economic stability in the long run. Our purpose of the article was to determine the impact of Ukrainian migration on the development of the economic component of European countries. We began by analysing migration trends by country, identifying the sharp increase in migrants to Europe and the transport routes for crossing the border, and the European countries' financial challenges due to migrants, which indicated an uneven distribution of migrants in European countries. The methodology of the empirical research was based on theoretical analysis of scientific literature on migration issues; methods: Analysis and synthesis; systemic; comparative; historical; Pareto principle; and expert assessments of numerous statistical reports of international data. The results pointed to the largest migration of the Ukrainian population in history caused by the war in Europe. Various EU support programs for Ukrainian migrants contributed to increasing the labour force, population growth in Europe, and the economic well-being of the European countries' populations. As a result, 2 hypotheses were tested, which revealed: 1Н: European countries' economy is developing due to the migration of the Ukrainian population to Europe; 2Н: Ukrainian refugees have been integrating successfully since the beginning of the war in Europe. The originality of the study was determined by the development of the Scheme of generalised efficiency of implementation of the directions of the «Programme of simplified legalisation in the EU for Ukrainians», the directions of which will enable the formation of a new economic model of reforms in the European Union, which will create favourable conditions for the legalisation and further integration of Ukrainian migrants in the EU, thereby contributing to the welfare of migrants and the development of European countries.